Update on poly(ADP-ribose) polymerase inhibitors resistance in ovarian cancer - Dong, Ruihong; Ding, Ting; Li, Zhengyu (Frontiers in Pharmacology, 2023)
Ovarian cancer is one of the most common reproductive system tumors, and the incidence of ovarian cancer in China is on the rise. Poly ADP-ribose polymerase (PARP) inhibitors (PARPi) is a DNA repair enzyme associated with DNA damage repair. PARPi takes PARP as a target to kill tumor cells, especially for tumors with homologous recombination (HR) dysfunction. Currently, PARPi has been widely used in the clinic, mainly for the maintenance of advanced ovarian epithelial cancer. With the wide application of PARPi, the intrinsic or acquired drug resistance of PARPi has gradually become an important clinical problem. This review summarizes the mechanisms of PARPi resistance and the current progress on PARPi-based combination strategies.